2018
DOI: 10.1007/s00425-018-3057-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic modification of western wheatgrass (Pascopyrum smithii) for the phytoremediation of RDX and TNT

Abstract: Contamination, from the explosives, hexahydro-1, 3, 5-trinitro-1, 3, 5-triazine (RDX) and 2, 4, 6trinitrotoluene (TNT), especially on live-fire training ranges, threatens environmental and human health. Phytoremediation is an approach that could be used to clean-up explosive pollution, but it is hindered by inherently low in planta RDX degradation rates, and the high phytotoxicity of TNT. The bacterial genes, xplA, and xplB, confer the ability to degrade RDX in plants, and a bacterial nitroreductase gene nfsI,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Few genetic transformation protocols and no genome editing studies have been reported for T. intermedium [66]. To increase the gene transformation efficiency, both Agrobacteriummediated and biolistic transformation methods need to be optimized and established in T. intermedium.…”
Section: Strategies For Targeted Mutagenesismentioning
confidence: 99%
“…Few genetic transformation protocols and no genome editing studies have been reported for T. intermedium [66]. To increase the gene transformation efficiency, both Agrobacteriummediated and biolistic transformation methods need to be optimized and established in T. intermedium.…”
Section: Strategies For Targeted Mutagenesismentioning
confidence: 99%
“…Phytoremediation can be a reliable, cost-efficient and vastly socially acceptable technology for dealing with contaminated lands. To increase its efficiency new omics approaches has gained a lot of interest in recent years [34]. Our review shows, that such large omics data sets have already identified specific environmental conditions that shape the quantity and quality of microbial communities in soil.…”
Section: Discussionmentioning
confidence: 98%
“…Study showed that transformed plants removed significantly more RDX when compared to wild-type plants. Furthermore, these plants were also more resistant to TNT toxicity, and detoxified more TNT than wild-type plants [34].…”
Section: Species Contaminantmentioning
confidence: 95%
See 1 more Smart Citation
“…Etroploe) expressing a bacterial TNT-detoxifying nitroreductase . Further progress has since been made with RDX-degrading switchgrass (Panicum virgatum), wheatgrass (Pascopyrum smithii) and creeping bentgrass (Agrostis stolonifera) transformed with xplA, xplB and nfsI Zhang et al 2018Zhang et al , 2016. The next steps now require the development of transformation protocols for a broader range of plant species such as vetiver and miscanthus.…”
Section: Enhancing Phytodetoxification Through Genetic Modificationmentioning
confidence: 99%